TASK-BASED LEARNING FOR YOUNG LEARNERS: IMPROVING COMMUNICATION SKILLS IN EARLY ENGLISH EDUCATION AT SD 213LAPONGKODA - Achmad Fajar Muhammad; Restu Januarty; Rampeng; Nurwidyayanti; Andi irwandi; A. Rizal (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This study aims to explore the implementation of Task-Based Learning (TBL) in developing communication skills in early English language education at SD 213 Lapongkoda. TBL, which focuses on using practical and authentic tasks within the learning process, is expected to enhance speaking, listening, and social interaction abilities of young learners. The research investigates the effects of TBL on communication skills development among elementary school 213 Lapongkoda students through a series of engaging, real-life tasks. Findings indicate that TBL significantly increases student motivation and effectively enhances communication skills by offering opportunities for experiential learning and collaboration. This study suggests that integrating TBL in English language education is an effective strategy to prepare young learners for real-world communication challenges and to foster language acquisition through meaningful tasks.